2000
DOI: 10.1097/00006123-200010000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pattern of Tie-2 and Vascular Endothelial Growth Factor Receptor Expression in Human Cerebral Arteriovenous Malformations

Abstract: AVM vessels exhibited abnormal expression of Tie-2 and VEGF-Rs, both of which may contribute to the pathogenesis of AVMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 32 publications
2
66
1
1
Order By: Relevance
“…19,20,22 Studies of AVM tissue have shown increased endothelial cell proliferation and increased expression of angiopoietin-2 and vascular endothelial growth factor, which promote vascular destabilization and proliferation, respectively. 17 However, the exact triggering event that leads to increased and disorganized angiogenesis ultimately leading to AVM formation has not been identified. Mice with ALK1 deficiency develop de novo AVMs after angiogenic stimulation.…”
mentioning
confidence: 99%
“…19,20,22 Studies of AVM tissue have shown increased endothelial cell proliferation and increased expression of angiopoietin-2 and vascular endothelial growth factor, which promote vascular destabilization and proliferation, respectively. 17 However, the exact triggering event that leads to increased and disorganized angiogenesis ultimately leading to AVM formation has not been identified. Mice with ALK1 deficiency develop de novo AVMs after angiogenic stimulation.…”
mentioning
confidence: 99%
“…143 In brain AVMs, intranidal vessels are exposed to abnormally high blood flow that creates high shearing forces, which can similarly activate shearinduced genes. 40 Takagi and colleagues have shown that phosphorylated ERK is upregulated in the SMCs of the media layer in brain AVMs. The activation of this pathway signals SMC proliferation, which contributes to the vascular remodeling and growth/regression of these lesions.…”
mentioning
confidence: 99%
“…6,8,47,48 Investigators have suggested that abnormal angiogenesis may play a central role in AVM formation and progression and have indicated that vascular remodeling may be mediated by angiogenic factors. 12,20,52 In particular, vascular endothelial growth factor (VEGF), a potent endothelial cell mitogen, is thought to play a key role. Increased VEGF expression has been demonstrated in the endothelium, subendothelium, and adventitia of resected AVM specimens.…”
mentioning
confidence: 99%